Cardiac disease and advanced age increase the mortality risk following surgery for periprosthetic femoral fractures. (July 2017) - Märdian, S.; Perka, C.; Schaser, K-D.; Gruner, J.; Scheel, F.; Schwabe, P.
Abstract : Aims: Periprosthetic fracture is a significant complication of total hip and knee arthroplasty. This study aimed to describe the survival of patients sustaining periprosthetic femoral fractures and compare this with that of the general population, as well as to identify the factors that influence survival. Patients and Methods: A total of 151 patients (women: men 116:35, mean age 74.6 years, standard deviation 11.5) that sustained a periprosthetic fracture between January 2005 and October 2012 were retrospectively analysed. Epidemiological data, comorbidities, type of surgical management, type of implant, and mortality data were studied. Results: The mean survival time was 77 months (95% confidence interval 71 to 84; numbers at risk: 73) and was lower than that of the general population. The risk analyses showed that previous cardiac disease, particularly ischaemic heart disease, cardiac arrhythmias, and heart failure, age over 75 years and American Society of Anesthesiologists (ASA) scores above 3 were associated with a significantly higher mortality. Conclusions: Periprosthetic fractures carry a high risk of post-operative mortality. Our data demonstrate that advanced age (> 75 years) and previous cardiac disease are associated with a significantly higher risk of mortality. The ASA score is an appropriate instrument for risk stratification. Pre-operative cardiac status should be optimised before surgery. Cite this article: Bone Joint J 2017;99-B:921–6.